Rates of macular volume changes in different stages and courses of primary open-angle glaucoma - M. V. Panchenko; O. M. Honchar; H. Yu. Panchenko; I. V. Kitchenko (Journal of Ophthalmology)
Purpose: To examine macular volume changes as assessed by optical coherence tomography (OCT) and rates of these changes in different stages and courses of primary open-angle glaucoma (POAG). Material and Methods: Totally, 123 patients (191 eyes; 54 men and 69 women; age, 48 to 69 years) with POAG were included in the study and underwent examination. Of these eyes, 67 were found to have pre-perimetric glaucoma and 124, perimetric POAG. At 5 years after enrollment in the study, the rate of macular volume change was assessed in 118 eyes. Examination included routine eye examination, static automated perimetry and OCT. POAG was classified as progressive or stabilized on the basis of annual rate of mean deviation (MD) change. The control group comprised 27 healthy individuals (54 eyes). Results: Macular volume was smaller in patients with perimetric glaucoma than in those with pre-perimetric glaucoma and decreased with an increase in the stage of glaucoma. We found macular volume to be positively moderately correlated with the annual rate of MD change (r = 0.6649, p < 0.05). Throughout a five-year study period, there was a reduction in the macular volume in 52.8% of eyes with pre-perimetric glaucoma and 59.7% of eyes with perimetric glaucoma (p > 0.05). A reduction in the macular volume was seen significantly more frequently among eyes with progressive perimetric POAG than among eyes with stabilized POAG (67.8% versus 45.9%; χ2 = 4.46; р < 0.05). Conclusion: Macular volume positively moderately correlated with the annual rate of MD change in eyes with POAG. Macular volume was significantly smaller in eyes with perimetric POAG than in controls and eyes with preperimetric POAG, and significantly decreased with an increase in the stage of glaucoma. A reduction in the macular volume over time was almost 1.5 times more common in eyes with progressive perimetric POAG than in eyes with stabilized perimetric POAG.